1992
DOI: 10.1152/ajpheart.1992.262.3.h833
|View full text |Cite
|
Sign up to set email alerts
|

Neurally mediated renal vasoconstriction during isometric muscle contraction in cats

Abstract: The aim of this study was to determine if the reflex increase in renal sympathetic nerve activity (RSNA) during static (isometric) muscle contraction evokes renal vasoconstriction and decreases renal blood flow. RSNA, renal blood flow velocity, and arterial pressure were measured simultaneously during isometric contraction of the hindlimb triceps surae muscle in eight chloralose-anesthetized cats. A 1-min contraction was evoked by stimulating the peripheral ends of the cut L7 and S1 ventral roots. RSNA and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 0 publications
6
32
1
Order By: Relevance
“…With respect to the reflex adjustment of the sympathetic nervous system arising from the contracting muscles, static muscle contraction reflexly augments postganglionic sympathetic nerve activities to the heart, kidney, and skeletal muscle within 10 s from the onset of static muscle contraction evoked in anesthetized animals [1][2][3][4]10]. The rapid increase in cardiac sympathetic nerve activity contributes to an acceleration of cardiac rhythm [4], and the increase in renal sympathetic nerve activity contributes to renal vasoconstriction and a reduction in renal blood flow [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the reflex adjustment of the sympathetic nervous system arising from the contracting muscles, static muscle contraction reflexly augments postganglionic sympathetic nerve activities to the heart, kidney, and skeletal muscle within 10 s from the onset of static muscle contraction evoked in anesthetized animals [1][2][3][4]10]. The rapid increase in cardiac sympathetic nerve activity contributes to an acceleration of cardiac rhythm [4], and the increase in renal sympathetic nerve activity contributes to renal vasoconstriction and a reduction in renal blood flow [3].…”
Section: Discussionmentioning
confidence: 99%
“…Since the passive mechanical stretch of muscle in a physiological range can stimulate myelinated group III afferents rather than unmyelinated group IV afferents, a comparison in the reflex responses of sympathetic efferent nerve activity between the contraction and the mechanical stretch of skeletal muscle should lead to an insight into the afferent mechanisms in the contracting muscle. The mechanical stretch of muscle increases cardiac and renal sympathetic nerve activities to 85 and 51% of their responses observed during static contraction with the same tension development [1,3]. Regarding AdSNA, it increased immediately after the onset of static muscle contraction in anesthetized rats [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Sympathetic nerve activities (SNA) directed toward blood vessels in a variety of organs including kidney 36,37) , skeletal muscle 38) , and heart 39) , were increased when hindlimb skeletal muscle was continuously and statically contracted in anesthetized or unanesthetized decerebrate cats. Moreover, the roles played by the EPR-evoked sympathoexcitation in mediating renal vasoconstriction 40) and tachycardia 39) have been demonstrated. Of note, skin SNA was not reflexly increased by skeletal muscle contraction 41) , suggesting that the EPR-elicited sympathetic outflows are organ-specific.…”
Section: Exercise Pressor Reflex Arcmentioning
confidence: 99%
“…It was demonstrated in anesthetized cats that the blood pressure was reflexly elevated by passively stretching the triceps surae muscles, which did not generate any muscle metabolites 42) . Subsequent electrophysiological studies demonstrated stimulation of mechanically sensitive group III muscle afferents 43) , cardiac 39) and renal 40) SNA increases, as well as vagal withdrawal 44) , in response to muscle stretch in anesthetized or decerebrate cats. Human subjects also exhibited reflexly increased muscle SNA during passive muscle stretch 45) .…”
Section: Exercise Pressor Reflex Arcmentioning
confidence: 99%